Earth Observing Systems XIX 2014
DOI: 10.1117/12.2063321
|View full text |Cite
|
Sign up to set email alerts
|

The absolute radiometric calibration of the Landsat 8 Operational Land Imager using the reflectance-based approach and the Radiometric Calibration Test Site (RadCaTS)

Abstract: Landsat 8 was launched on 11 February 2013 as the newest platform in the Landsat program. It contains two Earthobserving instruments, one of which is the Operational Land Imager (OLI). OLI includes an onboard radiometric calibration system that is used to monitor changes in its responsivity throughout the mission lifetime, and it consists of Spectralon solar diffuser panels as well as tungsten lamp assemblies. External techniques are used to monitor both OLI and its calibration system, and they include lunar v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, the early ground-based vicarious radiometric calibration of Landsat-8/OLI is performed, and the results show that the comparison between the TOA spectral radiance obtained by the OLI and the ground-based measurements show exceptional agreement (bands 1-6 < 1%, band 7 < 5%) [15]. Czapla-Myers et al [16] used the reflectance-based approach and the radiometric calibration test site to examine the stability of the Landsat-8/OLI instrument, and the results show the TOA spectral radiance calculated by the two methods agree with the ground-based measurements (5% uncertainty for the reflectance-based approach, and 3%-4% uncertainty for the radiometric calibration test site method). In addition, practical and repeatable comparative analyses of the Landsat-7/ETM+ and the Landsat-8/OLI were conducted by Peng et al [17] from spectral bands and vegetation indices, and the results showed that the two sensors had high similarity (the R 2 was greater than 0.96) though subtle differences existed.…”
Section: Datamentioning
confidence: 99%
“…Furthermore, the early ground-based vicarious radiometric calibration of Landsat-8/OLI is performed, and the results show that the comparison between the TOA spectral radiance obtained by the OLI and the ground-based measurements show exceptional agreement (bands 1-6 < 1%, band 7 < 5%) [15]. Czapla-Myers et al [16] used the reflectance-based approach and the radiometric calibration test site to examine the stability of the Landsat-8/OLI instrument, and the results show the TOA spectral radiance calculated by the two methods agree with the ground-based measurements (5% uncertainty for the reflectance-based approach, and 3%-4% uncertainty for the radiometric calibration test site method). In addition, practical and repeatable comparative analyses of the Landsat-7/ETM+ and the Landsat-8/OLI were conducted by Peng et al [17] from spectral bands and vegetation indices, and the results showed that the two sensors had high similarity (the R 2 was greater than 0.96) though subtle differences existed.…”
Section: Datamentioning
confidence: 99%
“…The pattern walked by the instrument operator is determined by the satellite sensor that is being tested (Figure 1). The whiskbroom site has been used for sensors such as Landsat 7 Enhanced Thematic Mapper Plus (ETM+), 2 and the pushbroom sensor has been used for sensors such as the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), Landsat 8 Operational Land Imager (OLI), 33,34,36 and the RapidEye constellation of satellites. 37 The large-footprint site is typically used for sensors with pixel sizes that are greater than 250 m, such as the Moderate Resolution Imaging Spectroradiometer (MODIS), 38 the Multiangle Imaging SpectroRadiometer (MISR), 39 and the Advanced Very High Resolution Radiometer (AVHRR).…”
Section: Reflectance-based Approachmentioning
confidence: 99%
“…30,31 Currently, the field work performed by RSG is a combination of traditional manned field campaigns, which are supplemented by RadCaTS. Work is still underway to understand any biases that may occur between the two methods, and this includes both the surface reflectance measurements, [32][33][34] as well as the atmospheric measurements. This paper describes preliminary work that compares the atmospheric measurements made by the traditional automated solar radiometer 35 (ASR) that is typically brought to the test site during a field campaign to those made by an AERONET Cimel sun photometer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the early ground-based vicarious radiometric calibration of the Landsat-8/OLI is performed, and the results show that the comparison between the TOA spectral radiance obtained by OLI and the ground-based measurements show exceptional agreement (bands 1-6 < 1%, band 7 < 5%) [17]. Jeffery et al [21] use the reflectance-based approach and the Radiometric Calibration Test Site to examine the stability of the Landsat-8/OLI instrument, and the results show the TOA spectral radiance calculated by the two methods agrees with the ground-based measurements (5% uncertainty for the reflectance-based approach, and 3%-4% uncertainty for the Radiometric Calibration Test Site method). In addition, practical and repeatable comparative analyses of the Landsat-7/ETM+ and the Landsat-8/OLI were conducted by Peng et al [22] from spectral bands and vegetation indices, and the results showed that the two sensors had high similarity (the R 2 was greater than 0.96) though subtle differences existed.…”
Section: Oli Imagerymentioning
confidence: 99%